Acceptability and iron content mochi filled red beans and raisins - Siregar, Fitra Nadhilla; Susanti, Nofi; Tanjung, Nadya Ulfa (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: In 2018, 32% of teenagers in Indonesia experienced anemia due to iron deficiency. Adolescence is one of the periods characterized by accelerated growth and development, leading to increased iron requirements in the body. Healthy and nutritious foods, including snacks, can be significant contributors to meeting the nutritional needs of iron-deficient teenagers. Red beans and raisins are among the food ingredients that can increase iron levels in the body; therefore, these food ingredients can be processed into the filling of a mochi that contains relatively high iron content.Objectives: The aim of this study is to determine the acceptance and iron content of red bean and raisin-filled mochi.Methods: This research is an experimental study. Acceptance testing was conducted organoleptically using a hedonic test method. The acceptance testing was conducted on 30 untrained panelists, namely female teenagers from SMAS Kesuma Bangsa Londut, and nutritional content analysis was performed at the Medan Industrial Research and Standardization Institute Laboratory. This research was conducted from January to March 2024.Results: Organoleptic test results showed that the panelists liked the color, aroma, texture, and taste of the red bean and raisin-filled mochi. The iron content test results in 120 grams of the product showed 37.4 mg. The red bean and raisin-filled mochi given to the panelists was 30 grams, meaning it contained 9.35 mg of iron.Conclusions: Red bean and raisin-filled mochi have good acceptance among teenage girls and also contain relatively high iron content.